2002
DOI: 10.1111/1540-6261.00416
|View full text |Cite
|
Sign up to set email alerts
|

The World Price of Insider Trading

Abstract: The existence and the enforcement of insider trading laws in stock markets is a phenomenon of the 1990s. A study of the 103 countries that have stock markets reveals that insider trading laws exist in 87 of them, but enforcement-as evidenced by prosecutions-has taken place in only 38 of them. Before 1990, the respective numbers were 34 and 9. We find that the cost of equity in a country, after controlling for a number of other variables, does not change after the introduction of insider trading laws, but decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
336
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,022 publications
(364 citation statements)
references
References 32 publications
21
336
0
7
Order By: Relevance
“…Thus, strong investor protection should be associated with more active foreign markets. We measure insider trading protection by a dummy variable set to zero before insider trading laws are enforced and one thereafter, using the data in Bhattacharya and Daouk (2002). Shareholder protection, instead, is measured on a discrete scale between zero (lowest protection) and six (highest protection), and is drawn from La Porta et al (1998).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Thus, strong investor protection should be associated with more active foreign markets. We measure insider trading protection by a dummy variable set to zero before insider trading laws are enforced and one thereafter, using the data in Bhattacharya and Daouk (2002). Shareholder protection, instead, is measured on a discrete scale between zero (lowest protection) and six (highest protection), and is drawn from La Porta et al (1998).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Kusnadi (2015) concludes that managers engage in projects that are riskier when more effective corporate governance is in place, and potentially improves shareholder value. Budsaratragoon et al (2012) investigate whether the requirement to report insider trades is effective in an emerging market such as Thailand, an issue highlighted in prior work such as Bhattacharya and Daouk (2002) and Gilbert and Tourani-Rad (2008). That is, the enactment of regulation will have negligible effects on the trading by insiders if surveillance mechanisms are not in place or if regulation is not enforced.…”
Section: Restrictions On Trading By Insidersmentioning
confidence: 99%
“…A seminal paper in the area by Bhattacharya and Daouk (2002) examines the enforcement of insider trading laws in 103 countries and how enforcement affects the cost of equity in a country.…”
Section: Restrictions On Trading By Insidersmentioning
confidence: 99%
“…Perotti and van Oijen (2001) have also reported that political instability often results in lower stock returns. A second way in which institutional and political factors can affect financial flows is by raising monitoring costs and the frequency of insider and other unfair trading practices (Bhattacharya and Daouk, 2002). Conversely, Papaioannou (2004) has pointed out that a high-quality legal system minimizes monitoring costs while bureaucratic and judicial efficiency alleviates agency costs by settling disputes arising from contract incompleteness.…”
Section: Literature Surveymentioning
confidence: 99%